Long-term outcomes of extracapsular tonsillectomy in the treatment of obstructive sleep apnoea in adults - Knubb, Jenny; Sjöblom, Henrik M.; Ikonen, Ella; Suomela, Miika; Piitulainen, Jaakko M. (Informa UK Limited, 2026)
Background
Tonsillectomy is an effective treatment option for obstructive sleep apnoea in selected adult patients, but there has been a lack of long-term follow-up data.
Objectives
To analyse the long-term outcomes of extracapsular tonsillectomy in the treatment of obstructive sleep apnoea in adults, with the longest follow-up periods to date.
Materials and methods
We recruited adults who had undergone extracapsular tonsillectomy because of obstructive sleep apnoea between 2004 and 2018 in the Hospital District of Southwest Finland. A new home sleep study, questionnaires, and a structured phone interview were conducted on these patients 4–17 years after surgical treatment. The primary outcome was the change in the apnoea-hypopnoea index.
Results
The mean apnoea-hypopnoea index was reduced from 27.1 preoperatively to 14.1 after the long-term follow-up (mean 12 years), and the mean Epworth Sleepiness Scale score decreased from 9.2 to 4.6. The long-term surgical success rate was 38.5%. Four out of five patients would choose the surgery again according to the phone interview.
Conclusions and significance
This study supports the notion that extracapsular tonsillectomy alone can be considered as a surgical treatment option for selected adults with obstructive sleep apnoea and tonsillar hypertrophy. For most of the patients, the obstructive sleep apnoea is alleviated.